Design and performance of the South Pole Acoustic Test Setup - Abdou, Y.; Becker, K.; Berdermann, J.; Bissok, M.; Bohm, C.; Böser, S.; Bothe, M.; Carson, Michael; Descamps, F.; Fischer-Wolfarth, J.; Gustafsson, L.; Hallgren, A.; et al. (2012)
The South Pole Acoustic Test Setup (SPATS) was built to evaluate the acoustic characteristics of the South Pole ice in the 10–100 kHz frequency range, for the purpose of assessing the feasibility of an acoustic neutrino detection array at the South Pole. The SPATS hardware consists of four vertical strings deployed in the upper 500 m of the South Pole ice cap. The strings form a trapezoidal array with a maximum baseline of 543 m. Each string has seven stages equipped with one transmitter and one sensor module (glaciophone). Sound is detected or generated by piezoelectric ceramic elements inside the modules. Analogue signals are sent to the surface on electric cables where they are digitized by a PC-based data acquisition system. The data from all strings are collected on a central computer in the IceCube Laboratory from where they are sent to a central data storage facility via a satellite link or stored locally on tape. A technical overview of SPATS and its performance is presented.